Distribuição Geográfica das ocorrências fossilíferas em Uberaba: uma análise crítica para a geoconservação - PINTO, Debora Gabriele dos Santos (2020)
The city of the Uberaba has national prominence in the fossil record of the continental Cretaceous, there are thousands of fossils identified, with description of species discovered around the municipality, with occurrences even in urban areas. The great importance of the Uberaba paleontological assembly generates the need for actions that guarantee the geoconservation of the existing geological heritage. Given this reality, this research sought to map the fossiliferous localities of the Uberaba as a way of promoting the analysis of geoconservation actions in the municipality. To this end, a bibliographic analysis of scientific publications on fossils in the area comprised by the municipality was carried out, as a way to locate the findings, quantifying the taxa described and scientific publications. The compilation of information about fossils demonstrated the advances in scientific research on the topic in the city, but also highlighted the need to develop measures that educate and involve the local community so that geoconservation actions are indeed effective in the municipality and that in fact generate a feeling of belonging in the citizens.